Creep fatigue crack growth and fracture mechanisms of T/P91 power plant steel. (May 2015) - Bassi, F.; Foletti, S.; Lo Conte, A.
Abstract : High temperature assessment of crack like defects in power plant components is one of the most important task to ensure high energy conversion efficiency. Creep fatigue crack growth tests for P91 power plant steel, conducted at 600°C on standard C(T) specimens with 0·1, 1 and 10 h hold times, are presented. Microscopic features of the creep fatigue damage were observed along the crack path, on polished and etched cross sections of the tested specimens. The dominant damage mechanism is the formation of microvoids and microcracks associated with the crack tip, due to the creep effect during the hold time. In order to predict the experimentally measured crack growth rate a simple summation rule is used. The superposition of fatigue crack growth rate and creep crack growth rate, experimentally obtained on the same batch of material used for creep fatigue crack growth tests, well describes the behaviour under creep fatigue loading.